Comparative evaluation of octenidine with chlorhexidine mouthwash in gingivitis and periodontitis patients: A randomized clinical trial - Amrita Amrita; Prerna Agarwal; Manvi Chandra Agarwal; Ashutosh Agarwal; Jaishree Garg; Parth Mehra (Wolters Kluwer Medknow Publications, 2024)
Introduction: Chlorhexidine gluconate (CHX) has been still regarded as the most efficient mouthwash. Due to its recognized negative effects, it can only be used for a short duration. Octenidine dihydrochloride (OCT), an antiseptic substance found by Sterling Winthrop in the 1980s, has proven helpful in preventing the co-aggregation of dental plaque microbial invaders without disrupting the typical, healthy oral flora. However, there is very little research on octenidine's effectiveness as a mouthwash for preventing plaque. Therefore, this study is being conducted to examine the effectiveness of mouthwashes containing 0.1% Octenidine and 0.2% chlorhexidine. Methodology: In this clinical trial, subjects were divided into two groups, 60 patients each with gingivitis and periodontitis. Then, from each group, 30 patients were advised to use octenidine mouthwash, and 30 patients were prescribed chlorhexidine mouthwash as an adjunct to scaling and root planning. Clinical parameters like O'Leary plaque index, Bleeding index, Probing pocket depth, and clinical attachment loss were evaluated at baseline and after 3 months. Result: In both the gingivitis and periodontitis groups, the octenidine group significantly outperformed the chlorhexidine group in all clinical metrics. Conclusion: Octenidine showed better results in comparison to chlorhexidine with respect to all the above-mentioned clinical parameters. Hence, it can be considered a promising mouthwash for future therapeutic and research studies.